2005
DOI: 10.1007/s00216-005-3210-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of a stir-bar-sorptive extraction–liquid desorption–large-volume injection capillary gas chromatographic–mass spectrometric method for pyrethroid pesticides in water samples

Abstract: Stir-bar-sorptive extraction followed by liquid desorption and large-volume injection capillary gas chromatography with mass spectrometric detection (SBSE-LD-LVI-GC-MS), had been applied for the determination of ultra-traces of eight pyrethroid pesticides (acrinathrin, cypermethrin, deltamethrin, esfenvalerate, fenpropathrin, fenvalerate, and permethrin cis and trans isomers) in water samples. Instrumental calibration for selected-ion monitoring acquisition and conditions that could affect the SBSE-LD efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(44 citation statements)
references
References 36 publications
1
42
0
1
Order By: Relevance
“…1a). No longer times were evaluated, since several authors had point out that for periods higher than 60 min, no advantages were observed for volatile enrichment purposes [8,9]. Therefore, the extraction time of 60 min was set for further experiments.…”
Section: Interception Correlation Coefficients (R 2 ) P-value Of Lamentioning
confidence: 99%
See 4 more Smart Citations
“…1a). No longer times were evaluated, since several authors had point out that for periods higher than 60 min, no advantages were observed for volatile enrichment purposes [8,9]. Therefore, the extraction time of 60 min was set for further experiments.…”
Section: Interception Correlation Coefficients (R 2 ) P-value Of Lamentioning
confidence: 99%
“…In a preliminary study, different desorption solvents were tested for the back-extraction process, including MeOH and ACN, since they are the most used for LD of the semi-volatile compounds analysed by SBSE [6][7][8][9]. Nevertheless, this analytical approach needs a solvent switch step, i.e.…”
Section: Effect Of the Ld Conditionsmentioning
confidence: 99%
See 3 more Smart Citations